Distribution of serotypes of Listeria monocytogenes in chicken meats in Turkey - SAHIN, S.; KALIN, R.; MOGULKOC, MN (Journal of the Hellenic Veterinary Medical Society, 2020)
Listeria monocytogenes is one of the important causes of food-borne infections. This study was conducted to determine the presence of L. monocytogenes and its serotype distribution in a total of 400 packaged chicken meat products (drumstick, breast, wing, and whole chicken) from different national companies. L. monocytogenes contamination was detected in 26.5% (106 in 400) of all samples when the products considered, drumsticks, breasts, wings, and whole chickens showed 47%, 15%, 35, and 9% positivity respectively. Four important serotypes of L. monocytogenes in human listeriosis (1/2a, 1/2b, 1/2c and 4b) were identified, and serotype 1/2a (94.3%) was determined as predominant in packaged chicken meats. The present study revealed that L. monocytogenes 1/2a serotype is prevalent in chicken meats and this may cause public health problems in Turkey. Further studies in poultry meats should be conducted on a large scale such as regional or national big markets to determine the presence of the pathogen and its dominant serotypes.